Impact of preeclampsia on megakaryocytopoesis and platelet homeostasis of preterm infants. (17th February 2016) - Yang, Jie; Zhang, HaiChun; Niu, JianMin; Mu, XiaoPing; Zhang, XiaoLing; Liu, Ying; Wang, JunPing; Chen, Yunbin
Abstract: The aim of this article is to investigate the megakaryopoyesis and thrombopoiesis in preterm infants born to mothers with preeclampsia and the potential effects mediated by soluble fms-like tyrosine kinase 1 (sFlt1) and thrombopoietin (TPO). A perspective case–control study was performed on 26 cord blood of preterm newborns born to mothers with preeclampsia (PE group) and 26 of preterms born to mothers without preeclampsia (control group). Circulating megakaryocyte count and megakaryocyte colony forming units (CFU-MK) were quantified by whole blood infiltration method and plasma clot culture system, respectively. Platelet activation markers, CD62P and CD63, were estimated by flow cytometry. Immunosorbent assays (ELISA) were employed to estimate plasma levels of sFlt1 and TPO of the two groups. When compared to the controls, infants born to mothers with PE had significantly lower peripheral platelet count (PE vs. controls: 157.9 [44.6] vs. 239.6 [57.5] × 10 9 /l, p  < 0.001), circulating MK count (5.8 [1.0] vs. 7.7 [0.9]/ml, p  < 0.001) and CFU-MK (14.1 [2.1] vs. 20.1 [2.8]/1 × 10 5 cell, p  < 0.001); greater expressions of CD62P (15.5 [2.3] vs. 11.4 [1.9]% platelets, p  < 0.001) and CD63 (12.3 [2.4] vs. 9.0 [1.6]% platelets, p  < 0.001); increased plasma Flt level (130.1 [8.0] vs. 97.7 [8.7] pg/ml, p  < 0.001) and TPO level (129.5 [17.8] vs. 98.9 [11.8] pg/ml, p  < 0.001). In PE group, sFlt instead of TPO showed a significantly negative relationship with platelet counts, CFU-MK and circulating MK count, a positive relationship with CD62P, CD63 expressions. In control group, both sFlt and TPO did not show any relationship with these parameters. sFlt played important role in megakaryocytopoesis and platelet homeostasis in preterm infants born to mothers with PE. Its mechanism maybe the effect of impaired megakaryocyte formation and increased platelet activation.